AUTOMATIC FISH FEEDING SCHEDULE SYSTEM USING ARDUINO AND REAL-TIME CLOCK - mansur, syaiful; Tiarto, Eko Hari; Aryanto, Iqbal May; Kinasih, Ayang; Zuhelmi, Tomy Pratama; Sintianingrum, Ayu (Universitas Lampung, 2025)
This research aims to design and develop an automated fish-feeding device using a microcontroller Arduino. This research intends to assist aquarium or fish farm owners in providing consistent and scheduled feeding while reducing the human workload. The research method involves designing both the hardware and software components. The hardware includes a feed dispenser, a motor drive, a Real-Time Clock (RTC) module, an LCD, and a microcontroller Arduino. The development of this software was to schedule feeding times and control the amount of feed dispensed. The research findings demonstrate the successful design and implementation of the automated fish-feeding device. Users can easily set feeding schedules and portion sizes through a user-friendly interface. In conclusion, this research has successfully designed a fish-feeding device using an Arduino microcontroller, which enhances the ease of fish maintenance in aquarium or fish farm environments, particularly in automated fish feeding.